Design and Build Smart Farming Automatic Plant Watering Based on the Internet of Things - Tegar Zaky Prasetyo, Tegar; umar (Emitor: Jurnal Teknik Elektro, 2024)
The agricultural sector is important in every country, especially in Indonesia, where the majority of the population are farmers. The problem faced in this modern era is that the agricultural system still uses traditional methods which are less efficient in the use of time. The main aim of this research is to make the agricultural sector more superior in Indonesia, to increase the efficiency of agricultural production using IoT (internet of things) technology. The research method used is by detecting the water content in the soil, temperature and humidity in the air and the weather on agricultural land. The tools and materials used are soil moisture sensors and ESP32. Soil moisture levels are also adjusted by irrigation using a water pump. If the soil humidity is below the limit, the humidity sensor will send information data to the ESP32 module and the data will be sent to the IoT (Internet of things) platform. ESP32 collects data from all sensors and connects the data to the cloud and displays it in Blynk. The results of this research were that the highest solar panel voltage read by the multimeter was 20.5 V and the lowest was 18.3 V. The soil moisture sensor can work according to commands, when the soil moisture condition is (< 50) the pump will turn on and when the soil condition is (> 50) the pump will not turn on. The INA219 sensor displays the voltage, current and power of the load when it is on or off. The average error read from the INA219 sensor voltage is 2.515%, the highest error is 5.6% and the lowest is 0.8%.